An educator's handbook for teaching about the ancient world. - Durgun, Pinar, (Archaeopress Publishing Ltd, 2020)
With the right methods, studying the ancient world can be as engaging as it is informative. Many K-12 teachers, university instructors, and museum educators use hands-on, project-based, and experiential activities in their classes to increase student engagement and learning. This book aims to bring together such pedagogical methods and teaching activities about the ancient world for any educator to use. The teaching activities in this book are designed in a cookbook format so that educators can replicate these teaching 'recipes' (which include materials, budget, preparation time, levels of students) in their ancient art, archaeology, social studies, and history classes. They can be implemented online or in-person, in schools, universities, libraries, museums, or at home.